The Effect of Consumer Satisfaction and Service Quality on Consumer Loyalty at CV. Maju Jaya - Selen Anggereyani; Dedy Lazuardi; Muammar Rinaldi; Ihdina Gustina; Adek apriyandi (Outline Journal of Management and Accounting, 2024)
This study aims to determine Customer Satisfaction and Service Quality on Consumer Loyalty at CV. Maju Jaya. The research population that will be used in this research is all customers who made purchases at the company during the 2021 period, totaling 173 customers. By using the Slovin formula with an error rate of 5%, a total sample of 121 respondents was obtained. The results of partial hypothesis testing show consumer satisfaction has a significant effect on consumer loyalty. The results of partial hypothesis testing show service quality has a significant effect on consumer loyalty. The results of simultaneous hypothesis testing show that Consumer Satisfaction, Service Quality has a effect on consumer loyalty. The result of the coefficient of determination shows that 56% which means that the Consumer Loyalty variable can be explained by the Consumer Satisfaction and Service Quality variables. The conclusions from the results of this study indicate that partially Customer Satisfaction has a significant effect on Consumer Loyalty. Service Quality has a significant effect on Consumer Loyalty. Simultaneously, Customer Satisfaction and Service Quality have a significant effect on Consumer Loyalty.